Depression in children with thalassemia major: prevalence and contributing factors - Venty Venty; Rismarini Rismarini; Dian Puspitasari; Yudianita Kesuma; Raden Muhammad Indra (Paediatrica Indonesiana, 2018)
Background Thalassemia major is a chronic disease requiring lifetime treatment. A recent study showed that 11-62% of thalassemia patients developed depression, which is associated with high morbidity and mortality. Understanding the extent of the problem related to depression and its contributing factors is important for early management. Objective To determine the prevalence and contributing factors for depression in children with thalassemia major. Methods This cross-sectional observational analytic study included thalassemia major patients aged 7 to <18 years in the Department of Child Health, Dr. Moh. Hoesin General Hospital (RSMH) in Palembang from June to July 2018 and had received blood transfusions at least 3 times. Subjects completed the Children's Depression Inventory (CDI) questionnaire. Depression was defined as a total score > 13. Data were analyzed using SPSS for Windows ver. 22.0. Results There were 64 patients included in this study, with mean age 12 (SD 3) years and 82.8% female. Most subjects came from families with low socio-economic status and low parental education. Deferiprone was the most commonly used type of iron-chelating agent. Depression was detected in 34.4% of respondents. Multivariate analysis revealed that factors affecting depression in children with thalassemia major were low maternal education (OR 4.014; 95%CI 1.066 to 15.112) and use of deferasirox (OR 4.129; 95%CI 1.168 to 14.601). Conclusion Prevalence of depression in children with thalassemia major is 34.4%. Low maternal education and deferasirox use as an iron-chelating agent are associated with depression in children with thalassemia major.